1963
DOI: 10.1128/jb.86.4.708-712.1963
|View full text |Cite
|
Sign up to set email alerts
|

Probable Identity of a Group D Hemolysin With a Bacteriocine

Abstract: Bloomington) AND JOSEPH M. DAVIE. Probable identity of a group D hemolysin with a bacteriocine. J. Bacteriol. 86:708-712. 1963.-All strains of Streptococcus zymogenes (S. faecalis var. zymogenes) produce a bacteriocine which is active against lactic acid bacteria and most other grampositive bacteria. Mutants which have lost the hemolytic characteristic lose at the same time their bacteriocine-producing ability. A strain which was resistant to the bacteriocine but which was nonhemolytic and nonbacteriocinogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 4 publications
3
41
0
1
Order By: Relevance
“…The authors further speculated that the bacteriocin and haemolysin produced by haemolytic E. faecalis were the same entity . The first evidence linking these two activities to a common physical entity was provided by Brock and Davie (1963), who showed that, after exposure to UV irradiation, the haemolysin and bacteriocin activities were simultaneously lost, and simultaneously regained by reversion. Granato and Jackson (1969) forwarded the first evidence that the cytolysin consists of multiple components.…”
Section: Initial Descriptions Of Toxin and Bacteriocin Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors further speculated that the bacteriocin and haemolysin produced by haemolytic E. faecalis were the same entity . The first evidence linking these two activities to a common physical entity was provided by Brock and Davie (1963), who showed that, after exposure to UV irradiation, the haemolysin and bacteriocin activities were simultaneously lost, and simultaneously regained by reversion. Granato and Jackson (1969) forwarded the first evidence that the cytolysin consists of multiple components.…”
Section: Initial Descriptions Of Toxin and Bacteriocin Activitiesmentioning
confidence: 99%
“…In this study, patients infected with cytolytic, gentamicin/kanamycin-resistant strains were at a fivefold increased risk of acutely terminal outcome regardless of the treatment regimen (of patients dying within 3 weeks of culture, 71% were infected with a cytolytic strain; Huycke et al ., 1991). Brock and Davie (1963) first suggested that the bacteriocin activity of the cytolysin might play a significant role in the virulence of enterococci by providing a competitive advantage to cytolytic strains over non-cytolytic strains, or other Gram-positive bacteria in the gastrointestinal tract, the likely staging ground for infection of distant anatomical sites (Hancock and Gilmore, 2000). They observed that cytolytic strains were able to outgrow non-cytolytic strains in vitro, even when the non-cytolytic strain was initially 100-fold higher in concentration (Brock and Davie, 1963).…”
Section: Role Of Cytolysin In E Faecalis Infection Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, enterococci have been reported to comprise a substantial component of the vaginal microbiota, particularly at the time of menses [16][17][18]. Pohunek [19] demonstrated that some streptococcal and (in particular) enterococcal strains were inhibitory to vaginal lactobacilli in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Streptococcus faecalis species are divided into subspecies on the basis of gelatinase production (S. faecalis subsp, liquefaciens) and hemolytic activity (S. faecalis subsp, zymogenes). The hemolytic activity (Hly) has been reported to be linked to bacteriocin production (Bcn) [1][2][3], to be transferred by conjugation at a high frequency into nonhemolytic and non-bacteriocinogenic strains of S. faecalis and to be coded for by plasmids with Mrs of 34. 10 6 to 38.…”
Section: Introductionmentioning
confidence: 99%